Reproductive Rights of Women in India: Exploring the challenges and implications of reproductive rights for women in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Marriage is an institute which combines not only two persons but two families. The basic function of marriage includes sexual pleasure and reproduction. Reproduction itself is complex process which involves various health issues right from the beginning. Reproduction not only deals with the birth of child but also with sexual relation, abortion, reproductive healthcare which includes use of contraception and sterilization. But still women do not have any right over their bodies. According to this survey 12.9 percent of married women aged between 19-49 years were not using any contraception and are at a risk of becoming pregnant or were pregnant with unwanted pregnancy. It is clear from this data that females are more suppressed in terms of their reproductive rights. Therefore it is very important to talk about the Reproductive Rights of Women.